Updates in the treatment of mantle cell lymphoma: A Canadian expert framework (Actualité hématologique au Canada, 2022)
Ce supplément est disponible seulement en anglais.Mantle cell lymphoma (MCL) is a B cell Non-Hodgkin Lymphoma that develops in the mantle zone of the lymph node. It is more common in men and is usually diagnosed at an advanced stage with involvement of lymph nodes, bone marrow, and potentially the gastrointestinal tract. MCL accounts for 5–10% of all new NHL cases per year in Canada, which is estimated at 11,400 for 2022. While most patients respond to initial treatment, relapses occur early and MCL generally shows a variable response to subsequent treatments, often with limited duration of benefit.Two main subtypes of MCL can be distinguished that arise from in situ MCL lesions. The most common subtype, classic MCL, arises from these cells with limited or no immunoglobulin heavy chain variable region (IGHV) mutations. Cells from this subtype express SOX11, are genetically unstable, and have naïve B cell-like characteristics. Classic MCL is more often nodal and extranodal and may eventually progress to aggressive blastoid or pleomorphic MCL. The other subtype, leukemic non-nodal MCL, arises from cells that have undergone IGHV somatic hypermutations, do not express SOX11, and exhibit characteristics of memory B cells. This subtype can have an indolent clinical behavior for a long time, often several years, but frequently acquires TP53 and other mutations and progresses to a more aggressive subtype.Treatment options have expanded significantly over the past decades, with improvements in both overall survival (OS) and progression-free survival (PFS) compared to earlier treatment eras. This Canadian expert framework aims to discuss the management considerations for patients with MCL, and will present both front-line treatment options as well as those for relapsed and refractory disease.